Zebrafish Spinal Cord Repair Is Accompanied by Transient Tissue Stiffening - Kharlamova, Maria A.; Hoche, Tobias; Taubenberger, Anna; Abuhattum, Shada; Kuscha, Veronika; Kurth, Thomas; Brand, Michael; Guck, Jochen; Möllmert, Stephanie (Biophysical Journal, 2020)
Severe injury to the mammalian spinal cord results in permanent loss of function due to the formation of a glial-fibrotic scar. Both the chemical composition and the mechanical properties of the scar tissue have been implicated to inhibit neuronal regrowth and functional recovery. By contrast, adult zebrafish are able to repair spinal cord tissue and restore motor function after complete spinal cord transection owing to a complex cellular response that includes axon regrowth and is accompanied by neurogenesis. The mechanical mechanisms contributing to successful spinal cord repair in adult zebrafish are, however, currently unknown. Here, we employ atomic force microscopy-enabled nanoindentation to determine the spatial distributions of apparent elastic moduli of living spinal cord tissue sections obtained from uninjured zebrafish and at distinct time points after complete spinal cord transection. In uninjured specimens, spinal gray matter regions were stiffer than white matter regions. During regeneration after transection, the spinal cord tissues displayed a significant increase of the respective apparent elastic moduli that transiently obliterated the mechanical difference between the two types of matter before returning to baseline values after the completion of repair. Tissue stiffness correlated variably with cell number density, oligodendrocyte interconnectivity, axonal orientation, and vascularization. This work constitutes the first quantitative mapping of the spatiotemporal changes of spinal cord tissue stiffness in regenerating adult zebrafish and provides the tissue mechanical basis for future studies into the role of mechanosensing in spinal cord repair.
CRIS-Team Scopus Importer:2022-08-03